2007
DOI: 10.1007/s00425-007-0668-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of plant glycoside hydrolases

Abstract: The functions of plant glycoside hydrolases and transglycosidases have been studied using different biochemical and molecular genetic approaches. These enzymes are involved in the metabolism of various carbohydrates containing compounds present in the plant tissues. The structural and functional diversity of the carbohydrates implies a vast spectrum of enzymes involved in their metabolism. Complete genome sequence of Arabidopsis and rice has allowed the classification of glycoside hydrolases in different famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
246
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(260 citation statements)
references
References 195 publications
(206 reference statements)
5
246
0
9
Order By: Relevance
“…Showalter, (1993 found that several proteins and enzymes are involved in the metabolic regulation and structural regulation of various cell-wall polymers. These enzymes include plant glycoside hydrolases, which perform numerous important functions in cell wall metabolism, mobilization of storage reserves, plant defence, signalling, and reorganization of glycans (Minic, 2008).…”
Section: Biochemical Estimationmentioning
confidence: 99%
“…Showalter, (1993 found that several proteins and enzymes are involved in the metabolic regulation and structural regulation of various cell-wall polymers. These enzymes include plant glycoside hydrolases, which perform numerous important functions in cell wall metabolism, mobilization of storage reserves, plant defence, signalling, and reorganization of glycans (Minic, 2008).…”
Section: Biochemical Estimationmentioning
confidence: 99%
“…By labeling apoplastic proteomes, we detected the active state of four putative bi-functional ␣-L-arabinofuranosidase/␤-D-xylosidases, two putative ␤-D-xylosidases, five putative ␤-D-glucosidases, two putative ␤-D-galactosidases, one putative heparanase, one putative ␤-D-glucanase, and one putative ␣-L-arabinofuranosidase. Glycosidases with these substratehydrolyzing activities process the major cell wall polysaccharides, including glucan, xylan, arabinoxylan, galactan, and arabinan, during cell wall assembly and reorganization (9). Thus glycosidase profiling reveals the active state of glycosidases that likely play a role in cell wall remodeling.…”
Section: Jjb Probes Label a Second Layer Of Glycosidasesmentioning
confidence: 99%
“…Genetic, molecular, and biochemical approaches revealed that glycosidases are localized in different cellular compartments and are important for various biological processes. The majority of plant glycosidases reside in the cell wall, and these enzymes can play major roles in cell wall restructuring (9). Other characterized glycosidases reside in other compartments to regulate glycosylation of proteins and hormones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and biochemical approaches are at present uncovering the individual enzymes responsible for building these macromolecules, and models of coordinated supramolecular assembly at the plasma membrane continue to evolve (Geisler et al, 2008;Liepman et al, 2010). Lastly, there is a growing interest in the roles of endogenous glycoside hydrolases in primary plant cell wall remodeling (Vicente et al, 2007;Lopez-Casado et al, 2008;Minic, 2008). Nonetheless, we are far from having a holistic model of cell wall development for even a single wall or tissue type (Somerville et al, 2004).…”
mentioning
confidence: 99%